Layered VOPO4 as a cathode material for rechargeable Zinc-ion battery : effect of polypyrrole intercalation in the host and water concentration in the electrolyte - Verma, Vivek (2021)
Rechargeable zinc-ion batteries (RZIB) present an interesting alternative to rechargeable Li-ion batteries. Among the active materials, layered vanadium-based oxides show a poor cell voltage but modifying this structure by attaching a phosphate group to the vanadium redox center can drastically enhance the cathode voltage. With this layered VOPO4 material, we demonstrate that pre-intercalating polypyrrole between crystallographic layers and using electrolyte with controlled water amounts are two absolutely essential conditions for easy and reversible Zn2+ (de)intercalation, thus vastly improving battery outputs and long-term capacity retention. We establish that the rational design of open-layered structures hinges imperatively on factors like host structural integrity and electrode-electrolyte compatibility in delivering the performance of multivalent-ion batteries.